Impact of climate change on future rice production in the Mekong River Delta - Nguyen Huu Quyen; Trinh Hoang Duong; Bui Tan Yen; Sebastian, Leocadio S. (2018)
The Mekong River Delta (MRD) region of Vietnam contributes 15% of the world’s rice exports (2018 rice export was 5.7 million tons of milled rice valued at about USD 2.54 billion). Therefore, rice production of the region does not only mean to country’s economy but also to global food security. The MRD, however, is among the climate change hotspot where rice production is affected by multiple climate-related risks. In support of developing recommendations for sustainable and adaptive rice production, estimations of future rice yield and production under different climate change scenarios (RCP4.5 and RCP8.5) were done for each of 13 MRD provinces. The ORYZA model with validated parameters and projected climate data was run for most common rice varieties. The estimated rice yield was then deducted for the projected El Niño and La Niña years based on yield reduction ratios obtained from analyses of historical yield and climate data. Finally, seasonal rice production of provinces was calculated based on the estimated yield and the climate-related risk maps. The results showed an increase in both precipitation and temperature from 2020 to 2050 due to the impacts of climate change may reduce rice yields of the MRD. Rice yield reduction will be largest during the winter-spring season and smallest during the autumn-winter season. In case of ENSO events, rice yield can be reduced by over 60% in coastal provinces during the winter-spring season and around 40% in upstream provinces during the autumn-winter season. These results suggest the need to change cropping system and shift cropping calendars together with other structural measures to better adapt and mitigate future impacts of climate change and extreme climate events.